Does terrorism affect the stock market returns and volatility? Evidence from Pakistan's stock exchange. Issue 1 (19th August 2020) - Khan, Dilawar; Ullah, Arif; Alim, Wajid; Haq, Ihtisham ul
Abstract : During the last few decades, the number of terrorist's attacks has been increased to a great extent in the world, which possibly enhances the fear of investors and influences long‐term investment commitments. It is important to explore how the financial market reacts to terror events in order to dictate the suitable policy recommendations. This study examines whether terrorism exerts a significant effect on stock market returns and volatility by examining the daily time series data for Pakistan from the period Oct 7, 1999 to May 31, 2016. The employed econometric techniques in this study are the generalized autoregressive conditional heteroskedasticity (GARCH) and the exponential generalized autoregressive conditional heteroskedasticity (EGARCH) models. The GARCH and EGARCH results confirm that terrorism has a significant effect on both the stock market returns and volatility in Pakistan. In addition, the EGARCH results also conclude that the negative shock (terror news) creates higher volatility as compared to positive shock (good news) in the stock market. The outcomes suggest that terror events significantly affect financial investors in the stock markets. The paper suggests that terror risk is an influential cognitive factor in describing the stock market returns and volatility. Terror must be addressed in order to achieve desirable stability in financial markets.